THE SIGNIFICANCE OF THE TASKS OF THE PISA INTERNATIONAL PROGRAM IN THE TEACHING OF BIOLOGICAL SCIENCES - Doniyorov Mukhiddin Normamatovych (Journals Park Publishing, 2023)
The article describes the educational importance of using international assessment studies in the biological education system, the purpose of implementing biology PISA research tasks in secondary schools, and its role in the education system. Also, opinions on the development of students' knowledge of PISA tasks are presented. This is where studying the PISA program is important.
Keywords: PIRLS, TIMSS, PISA, TALLIS, natural sciences, literacy, biology, assistant, heredity, national center.